Familial hypercholesterolemia: Molecular characterization of possible cases from the Azores Islands (Portugal) - Cymbron, T. (2014)
Familial hypercholesterolemia (FH) is an autosomal dominant disorder of the cholesterol metabolism, which constitutes a risk factor for coronary arterial disease (CAD). In the Azores Islands (Portugal), where mortality from CAD doubles its rate comparatively to the rest of the country and where a high frequency of dyslipidemia has been reported, the prevalence and distribution of FH remain unknown. The molecular characterization of a group of 33 possible cases of FH of Azorean background was undertaken in this study. A DNA array was initially used to search mutations in the LDLR, APOB and PCSK9 loci in 10 unrelated possible cases of FH. No mutations were detected in the array; after sequencing the full LDLR gene, 18 variants were identified, corresponding to two missense (c.806G > A; c.1171G > A) and sixteen synonymous alterations. Six of the synonymous variants which are consistently described in the literature as associated with altered cholesterol levels were used to build haplotypes. The most frequent haplotype corresponded to TTCGCC (45%), a "risk" haplotype, formed exclusively by alleles that were reported to increase cholesterol levels. Some of the variants detected in the full sequencing of the LDLR gene fell within the ligand-binding domain of this gene, defined by exons 2 to 6. To add information as to the role of such variants, these exons were sequenced in the remaining 23 possible FH cases. Two missense alterations (c.185C > T; c.806G > A) were found in this subset of possible FH cases. The missense alteration c.185C > T, identified in one individual, is novel for the Portuguese population. In silico analysis was not conclusive for this alteration, whose role will have to be further investigated. This study represents the first approach to the establishment of the mutational profile of FH in the Azores Islands.